The Role of the European Society of Human Genetics in Delivering Genomic Education - Tobias, Edward S.; Avram, Elena; Calapod, Patricia; Cordier, Christophe; den Dunnen, Johan T.; Ding, Can; Dolzan, Vita; Houge, Sofia Douzgou; Lynch, Sally Ann; O’Byrne, James; Patsalis, Philippos; Prokopenko, Inga; et al. (Frontiers in Genetics, 2021)
The European Society of Human Genetics (ESHG) was founded in 1967 as a professional organisation for members working in genetics in clinical practice, research and education. The Society seeks the integration of scientific research and its implementation into clinical practice and the education of specialists and the public in all areas of medical and human genetics. The Society works to do this through many approaches, including educational sessions at the annual conference; training courses in general and specialist areas of genetics; an online resource of educational materials (EuroGEMS); and a mentorship scheme. The ESHG Education committee (EduComm) is considering, and already implementing, new approaches to expand the reach of its educational activities and portfolio. With changes in technology, appreciation of the utility of genomics in healthcare and the public and patients’ increased awareness of the role of genomics, this review will summarise how the ESHG is adapting to deliver additional educational activity.